Noninvasive, objective evaluation of lower extremity lymphedema severity using shear wave elastography: A preliminary study. Issue 12 (December 2021) - Akita, Shinsuke; Yoshida, Kenji; Omura, Masaaki; Yamaji, Yoshihisa; Tezuka, Takafumi; Tokumoto, Hideki; Azuma, Kazuhiko; Ikehara, Yuzuru; Yamaguchi, Tadashi; Mitsukawa, Nobuyuki
Summary: Background: Increased skin and subcutaneous tissue stiffness in patients with early-stage lymphedema has been reported. The purpose of this study was to examine the use of shear wave elastography (SWE) for evaluating lower extremity lymphedema (LEL). Methods: For 10 lower extremities of normal controls and 72 limbs of patients with gynecological cancer whose lymphatic function was categorized into six stages based on the range of dermal backflow (DBF) observed in indocyanine green (ICG) lymphography, SWE was performed and shear wave velocity (SWV) of the dermis and three layers of subcutaneous tissue at the thigh and calf were recorded. Twenty-five patients underwent thigh tissue histological and dermal thickness examinations. Results: The strongest correlation between the ICG DBF stage and SWV during SWE was observed on the dermal layer of the thigh ( p < 0.01, R = 0.67). There was a significant correlation between the dermal thickness of the thigh and the ICG DBF stage ( p < 0.01, R = 0.87) and also between the dermal thickness of the thigh and SWV ( p < 0.01, R = 0.73). Conclusion: Noninvasive, objective evaluation of LEL severity using SWE was well correlated with lymphatic function as determined by ICG lymphography. The DBF changes in the dermis of the thigh best reflected the changes in lymphatic function. Dermal thickness variations may partially account for differences in SWV.